Disclosure of sexual orientation in men who have sex with men in China: a cross-sectional survey. (October 2016) - Tang, Weiming; Mao, Jessica; Tang, Songyuan; Liu, Chuncheng; Mollan, Katie; Wong, Terrence; Zhang, Ye; Hudgens, Michael; Qin, Yilu; Ma, Baoli; Liao, Meizhen; Yang, Bin; et al.
Abstract: Background: Most men who have sex with men (MSM) in China do not publicly disclose their sexual orientation. This low rate of disclosure may affect sexual behaviours, testing for HIV or other sexually transmitted infections (STIs), and disease transmission. This study examined factors associated with overall sexual orientation disclosure and disclosure to a healthcare professional. Methods: We did a cross-sectional online survey of MSM in China from September 23, 2014, to October 8, 2014, through three national websites. Participants completed questions covering sociodemographic information, sexual behaviors, HIV and syphilis test history, and self-reported HIV status. We defined overall disclosure as having ever disclosed sexual orientation to anyone other than a sexual partner, and healthcare professional disclosure as disclosing to a doctor or other medical provider. Eligible participants gave informed consent electronically before beginning the survey. Findings: A total of 1819 men started the survey and 1424 (78%) completed it. Of 1424 participants, 62% (886/1424) reported overall disclosure, and 16% (232/1424) had disclosed to healthcare providers. In multivariate analyses, the odds of overall sexual orientation disclosure were 56% higher among MSM who used smartphone-based sex-seeking applications (adjusted OR 1·56 [95% CI 1·25–2·95]), but were lower among MSM reporting high-risk sexual risk behaviors such as sex while drunk (0·55 [0·37–0·81]) and sex while using drugs (0·66 [0·50–0·87]). The odds of disclosure to a healthcare professional were greater among MSM who had ever been tested for HIV (3·36 [2·50–4·51]) or STIs 4·92 [3·47–6·96]) or self-reported as HIV positive (1·59 [0·93–2·72]). Interpretation: More than 80% of MSM surveyed had not disclosed their sexual orientation to health professionals. This low level of disclosure probably represents a major obstacle to serving the unique needs of MSM in clinical settings. Further research and action to facilitate disclosure of sexual orientation by MSM, especially to healthcare professionals, is urgently needed. Funding: US National Institute of Allergy and Infectious Diseases (NIAID; 1R01AI114310); University of North Carolina (UNC)-South China STD Research Training Centre (Fogarty International Centre 1D43TW009532); UNC Center for AIDS Research (NIAID; 5P30AI050410); University of California San Francisco Centre for AIDS Research (NIAID; P30 AI027763]; US National Institute of Mental Health (R00MH093201); UNC Chapel Hill, Johns Hopkins University, Morehead School of Medicine and Tulane University (UJMT) Fogarty Fellowship (FIC R25TW0093); Doris Duke International Clinical Research Fellowship; US National Center for Advancing Translational Sciences (UL1TR001111).